BCT 2022
DOI: 10.56632/bct.2022.1101
|View full text |Cite
|
Sign up to set email alerts
|

Developing New Software to Analyze the Emo-‎Sensory Load of Language

Abstract: Technology plays a crucial role in fully understanding all aspects ‎of language and uncovering the hidden patterns, such as sense and emotion ‎density in texts. Yet, it seems that remarkable attention has not been paid to ‎the sensory and emotional loads of learning texts as the primary source of ‎learning. This study attempts to present an objective way of analyzing ‎English learning texts from both emotional and sensory perspectives to ‎provide material developers to measure the emotional and sensory loads o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Furthermore, developing teachers' manuals with supplementary activities and material can enhance learning among the mentally challenged. Akbari and Pishghadam (2022) proposed a new kind of software for assessing texts from both emotional and sensory viewpoints. Researchers can create a similar program to evaluate the sensory load of textbooks written for mentally-challenged learners.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, developing teachers' manuals with supplementary activities and material can enhance learning among the mentally challenged. Akbari and Pishghadam (2022) proposed a new kind of software for assessing texts from both emotional and sensory viewpoints. Researchers can create a similar program to evaluate the sensory load of textbooks written for mentally-challenged learners.…”
Section: Discussionmentioning
confidence: 99%
“…In today's psychological landscape, many different theories of intelligence, such as IQ, EQ, and SQ, have been developed. ESQ is a new framework for integrating classical EQ and SQ conceptions of intelligence, referring to the ability of individuals to recognize, label, monitor, and manage senseinduced emotions and establish emo-sensory communication (Akbari & Pishghadam, 2022;Pishghadam et al, 2016;Pishghadam & Shayesteh, 2017). Pishghadam et al (2020) introduced ESI as a conciliatory approach and a leading factor in daily life, defining it as sensitivity to emotions evoked by sensory inputs.…”
Section: Discussionmentioning
confidence: 99%
“…So, generalizing these results for segment 1 and segment 2 should include the marketing plan (targeting and positioning) that differs for these two segments, and the answer is no. However, these results must be carefully analyzed when designing marketing materials to appeal to all stakeholders (Akbari & Pishghadam, 2022;Pishghadam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that marketing of these professional courses should fully utilize both traditional and digital marketing channels (particularly social media) to fully inform students of both the potential benefits of professional courses (regular webinar series) and the easy availability of key information such as courses/start dates/fees (this should be directly available on the college web site). There are also extreme preferences for the days of the week students would like to study (the finding of studying on Mondays, Tuesdays, and Wednesdays was highly preferred) (Akbari & Pishghadam, 2022;Pishghadam et al, 2016). Furthermore, there is a strong preference for face-toface study, and they generally want to study part-time (usually in the early evening)-this is not a surprising result as many people looking for professional courses will be working full-time during the day and maybe get married, starting a family or already have a family.…”
Section: Discussionmentioning
confidence: 99%